Budget of organic carbon in the North‐Western Mediterranean open sea over the period 2004–2008 using 3‐D coupled physical‐biogeochemical modeling. Issue 9 (24th September 2016) - Ulses, C.; Auger, P.‐A.; Soetaert, K.; Marsaleix, P.; Diaz, F.; Coppola, L.; Herrmann, M.J.; Kessouri, F.; Estournel, C.
Abstract: A 3‐D hydrodynamic‐biogeochemical coupled model has been used to estimate a budget of organic carbon and its interannual variability over the 5 year period 2004–2008 in the North‐Western Mediterranean Open Sea (NWMOS). The comparison of its results with in situ and satellite observations reveals that the timing and the magnitude of the convection and bloom processes during the study period, marked by contrasted atmospheric conditions, are reasonably well reproduced by the model. Model outputs show that the amount of nutrients annually injected into the surface layer is clearly linked to the intensity of the events of winter convection. During cold winters, primary production is reduced by intense mixing events but then spectacularly increases when the water column restratifies. In contrast, during mild winters, the primary production progressively and continuously increases, sustained by moderate new production followed by regenerated production. Overall, interannual variability in the annual primary production is low. The export in subsurface and at middepth is however affected by the intensity of the convection process, with annual values twice as high during cold winters than during mild winters. Finally, the estimation of a global budget of organic carbon reveals that the NWMOS acts as a sink for the shallower areas and as a source for the Algerian and Balearic subbasins. Key Points: A budget of organic carbon is estimated using 3‐D physical‐biogeochemical coupled modeling The interannual variability of primary production and downward export is assessed